Very good lives : the fringe benefits of failure and the importance of imagination - Rowling, J. K.; Holland, Joel (New York : Little, Brown and Company, 2015)
In 2008, J.K. Rowling delivered a commencement speech at Harvard University, now published for the first time in book form. Very Good Lives presents J.K. Rowling's words of wisdom for anyone at a turning point in life. Drawing from stories of her own post-graduate years, the author addresses some of life's most important questions.
Keywords: Failure (Psychology); Success; Fear; Anxiety; Imagination; Self-actualization (Psychology); Psychology, Applied; Baccalaureate addresses